2020
DOI: 10.21203/rs.3.rs-38971/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Features and Outcomes of COVID-19 in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Abstract Background Few studies have focused on exploring the clinical characteristics and outcomes of COVID-19 in older patients. We conducted this systematic review and meta-analysis to have a better understanding of the clinical characteristics of older COVID-19 patients.Methods A systematic search of PubMed and Scopus was performed from December 2019 to May 3rd, 2020.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…60 years and over. The higher risk of death in men and older adults is similar to global trends [ 40 , 41 ]. Apart from the higher contribution of men to comorbidities, other suggested reasons for their higher morbidity and mortality include behavioral, social and biological differences that favor women [ 40 ].…”
Section: Discussionmentioning
confidence: 75%
“…60 years and over. The higher risk of death in men and older adults is similar to global trends [ 40 , 41 ]. Apart from the higher contribution of men to comorbidities, other suggested reasons for their higher morbidity and mortality include behavioral, social and biological differences that favor women [ 40 ].…”
Section: Discussionmentioning
confidence: 75%
“…Most of the published studies examined the clinical features and outcomes of COVID‐19 in older adults. Current research mainly focused on the immediate and more pressing issues, such as the physiological presentations of COVID‐19 for older adults (Gan et al, 2020; Liu et al, 2020; Neumann‐Podczaska et al, 2020; Singhal et al, 2020). In comparison, literature about long‐term mental health issues of socially isolated older adults in COVID‐19 is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…As well as being at increased risk for symptomatic infections, it is apparent that older adults are at higher risk for mortality; the overall COVID‐19 mortality is reported to be 1.38%, rising sharply with age to 13.4% for those aged over 80 years, 15 with mortality rising to over 30% for those who are living with frailty 16 . In one meta‐analysis, it was reported that approximately half of all people over 60 years of age with COVID‐19 will experience a severe disease course, although the majority of included studies were based on cohorts admitted to hospital for COVID‐19 and thus likely do not represent the breadth of community cases 17 …”
Section: Introductionmentioning
confidence: 99%